COI Gene Variation of Pseudococcidae in Ornamental Plants Based on In Silico RFLP Method - Adelisa, Septi Nur; Hardiyanti, Ayu Tri; Rasyada, Almazahra Aulia; Angga, Zidane Bagus Bayu; Ritiau, Yeremia Ajijaya Putra; Lisdiana, Lisa (LenteraBio : Berkala Ilmiah Biologi, 2025)
Ornamental plants are susceptible to pest attacks that influence lowering the quality and quantity of plants, one of which is from the Pseudococcidae family. Pseudococcidae has many species that attack various types of plants due to genetic variation. Pseudococcidae pest detection methods are needed to develop prevention and treatment methods. The aim of the research is to analyze the genetic variation of the Pseudococcidae family based on the Cytochrome Oxidase Subunit I (COI) gene using the Random Fragment Length Polymorphism (RFLP) method in silico, so that it can become basic information for further research related to pest control through genetic approaches. The methods applied were screening restriction enzyme candidates to compare the restriction patterns of tested DNA sequence samples. Next, the in silico RFLP test had completed to analyze the nucleotide sequence using certain restriction enzymes to obtain polymorphism results in the form of differences in the length of the restriction fragments. The results of the research showed genetic variation (polymorphism) on the AluI (allele A1, A2, A3, A4, A5, A6, and A7 alleles) and BspHI (B1 and B2 alleles) restriction recognition site of the 12 COI gene sequences in PopSet: 262216777. This research shows that the restriction enzymes AluI and BspHI are able to identify genetic variations in the COI gene of the Pseudococcidae family. This information can help identify Pseudococcidae types and contribute to controlling Pseudococcidae pests on ornamental plants.